Sosio-Ecological Dynamic of Small Scale Fisheries in Prigi Trenggalek - Darmawan Ockto Sutjipto (JURNAL PERIKANAN DAN KELAUTAN, 2018)
Small scale fishing is a very important part of the fisheries sector. Not only play an important role in enhancing food security, but also becomes an absorbent for workers without the need for educational. Actors in the small-scale fishery, as defined by Law 45 of 2009, are fishermen who fish their daily needs with the largest size of 5 (five) Gross Register Tonnes (GT) of fishing boats. The fishermen of Prigi are dominated by small fishermen, where the fleet is no larger than 5 GT. The number of small-scale fishing gear in Prigi exceeds 60% of the total gear. The dominance of small-scale fisheries promotes good management with long-term goals, namely the sustainability of fisheries. Today's management of fisheries management has shifted from conventional management to community-based management. In order to support the community-based management of fisheries management, various information about the community, which is the policy objective, is needed. To this end, small-scale fisheries research in Prigi and strategies for the adaptation of the extended fishery fisheries were carried out. The method used is the snowball sampling method and the calculation of the diversity of catching resources. Fishermen who are the subject of the research are small-scale fishermen who operate ships under 5 GT. The gear is stretch fishing, gillnets and tonda fishing rods. There are small fishermen in Prigi who have different types of gear that are used at that time depending on the season of the fish. The selection of fishing gear by fishermen is likely to be caused by different expertise, skills and experience of fishermen in the operation of fishing gears. In addition, the capital held by fishermen to produce fishing gear and the economic level of the fish caught will also likely affect the fishers in choosing the type of fishing gear used each day. The adaptation strategies of fishermen to unpredictable catches are divided into two groups, namely the catch strategy and the search for alternative sources of income.